The Effect of Ethical Leadership and Work-Life Balance on Job Commitment, with Psychological Empowerment as a Mediating Variable, at Perumda Air Minum Tirta Tohlangkir in Karangasem Regency - Kadek Rara Ragita Cahyani; I Ketut Setia Sapta; I Nengah Suardhika (PT. Publikasiku Academic Solution, 2026)
This research aims to analyze the influence of ethical leadership and work-life balance on work engagement with psychological empowerment as a mediating variable at Perumda Air Minum Tirta Tohlangkir, Karangasem Regency. The background of this research is based on public service challenges and integrity issues that demand the strengthening of human resources through ethical leadership and work-life balance to increase employee dedication. This study used a quantitative explanatory approach. The population in this study were all employees of Perumda Air Minum Tirta Tohlangkir, Karangasem Regency, totaling 127 people. The sampling technique used was the saturated sampling method (census). Data were collected through questionnaires and analyzed using Structural Equation Modeling techniques based on Partial Least Squares (SEM-PLS) with SmartPLS 4.1 software. The results showed that: Ethical leadership has a positive and significant effect on psychological empowerment; Work-life balance has a positive and significant effect on psychological empowerment; Psychological empowerment has a positive and significant effect on work engagement; Ethical leadership has a positive and significant effect on work engagement; Work-life balance has a positive and significant effect on work engagement; Psychological empowerment is able to partially mediate the influence of ethical leadership on work engagement; and Psychological empowerment is able to partially mediate the influence of work-life balance on work engagement. These findings confirm that to increase employee work engagement in the public service sector, organizations need to strengthen leadership integrity, support employee life balance, and build autonomy and work meaningfulness through psychological empowerment.